A new method for image segmentation - Wang Guitang; Zhu Jianlin; Wei Qingchun; Xin Huasheng; Cao Peiliang (2009 Asia-Pacific Conference on Computational Intelligence and Industrial Applications, 2009)
On the basis of analyzing the blur images with noise, this paper presents a new segmentation method which is based on the morphology method, fuzzy K-means algorithm and some parts operator of the Canny algorithm. Because of the Canny's good performance on good detection, good localization and only one response to a single edge, we introduce the course of Canny operator that calculating the value and direction of grads, non-maxima suppression to the grad value and lag threshold process into our post-treatment process. Through experiments, it is demonstrated that the image segmentation method in this paper is very effective.